The Relationship Between Factors on Informal Learning and Transfer of Learning of Managerial Knowledge and Skills Among Head Nurses in Two Government Hospitals in Kelantan - Nik Mahmood, Nik Hasnaa (2005)
Today more and more organizations are seeking ways to establish continuous learning environment which requires organization to extend beyond formal training program to cultivate ongoing interaction among employees and to promote learning methods that are drawn upon employees previous experience. A central ingredient of continuous learning environment is informal learning. Hospitals are among the organizations that are committed to employees' continuous learning. Nurses are encouraged to continue to learn from their mistake and increase the quality of their care and services. The purpose of this study was to examine the role of informal learning in developing managerial knowledge and skills and transfer of learning among head nurses. Specifically, this study was undertaken to examine: (1) the learning activities mostly used by the head nurses to learn managerial skills; (2) the specific informal learning activities used by the head nurses to learn managerial skills; (3) the relationship between informal learning, motivation to learn and work environment and learning (i.e. level of knowledge and skills); (4) the relationship between informal learning, motivation to learn and work environment and transfer of learning; (5) the mediating role of learning (i-e. level of knowledge and skills) in the relationship between informal learning, motivation to learn, and work environment and transfer of learning; (6) the influence of informal learning, motivation to learn and work environment on learning (i.e. level of knowledge and skills) and (7) influence of informal learning, motivation to learn and work environment on transfer of learning. The theoretical framework which guides this study was Watkins and Marsick's (1990) theory of informal and incidental learning, Vroom's (1964) expectancy theory and Baldwin and Ford's (1988) transfer model. A total of 82 head nurses from two hospitals in the state of Kelantan participated in the study. Data were collected by the survey method. Data were analyzed using both descriptive and inferential statistics. Firstly, results of the descriptive statistics analysis revealed that head nurses gained managerial knowledge and learned managerial skills mostly from informal learning activities. Secondly, the specific informal learning activity used by head nurses to learn managerial skills were mostly learning from trial and error, learning from past experience, learning through mentoring, learning through observation, learning form interaction with others and learning through role-modeling. Thirdly, the results of the study showed a low and significant correlation between informal learning, motivation to learn, and work environment with level of learning and transfer of learning. Fourthly, level of learning was a good mediating variable for the relationship between informal learning, motivation to learn, work environment and transfer of learning. Finally, results of multiple regression analysis revealed that motivation to learn explains 15.5% variance in learning and 16.7 variance in transfer of learning whereas informal learning explain 12.2% of variance in level of learning and 13.4% of variance in transfer of learning. Theoretical and practical implications and contributions were discussed in Chapter 5.